A case for taking the dual role of counsellor-researcher in qualitative research. Issue 4 (1st October 2016) - Fleet, Doreen; Burton, Amy; Reeves, Andrew; DasGupta, Mani P.
ABSTRACT: There is ongoing debate about whether the challenges of practice-based research in counselling, with clients' discourses providing the raw data, can be overcome. This article begins by considering the argument of whether taking a dual role of counsellor-researcher within case study research is a legitimate qualitative approach. A case example using sand-tray in short-term therapy with adults from a pluralistic perspective is provided to demonstrate how the challenges of the dual role can be managed to produce effective research findings. It is suggested that this approach closes the gap between research and practice to produce findings that are highly relevant to the counselling context. The ethical considerations of taking a dual role of counsellor-researcher are considered, and opportunities and challenges when adopting this approach are identified.